Effects of the Extraction Methods on the Total Phenolic Content, the Total Flavonoid Content, and the Antioxidant Activity of the Mango (Mangifera indica L.) Leaf Extracts - Tinasy, Nur Audiyah; Wijayati, Nanik (Prodi Kimia, 2024)
Bad air conditions can be caused by cigarette smoke, industrial fumes, or vehicle exhaust gases. This condition can result in the emergence of free radicals. A free radical can cause a chain reaction that can damage tissue. This reaction can be dampened by compounds that are antioxidants. Mango leaf (Mangifera indica L.) contain flavonoids, alkaloids, saponins, and tannins. Flavonoid compounds are known to have the ability to act as antioxidants. Flavonoid compounds are highly unstable and can be significantly lost during various stages of processing. Therefore, an efficient extraction process is needed to maintain the compound content in natural ingredients. This research aims to analyze the optimal method that can produce total phenolic content, total flavonoids, and high antioxidant activity. The extraction methods used include ultrasonic wave-assisted extraction, reflux, and maceration. Determination of total phenolic content was carried out using the Folin-Ciocalteu reagent, total flavonoid content was carried out using the AlCl3 reagent, and antioxidant activity was carried out using the DPPH method. The results showed that the highest TPC was obtained by maceration extraction which produced a TPC of 218.86 ± 4.95 mgGAE/g, the highest TPC was obtained by reflux extraction which produced a TFC of 301.97 ± 30.07 mgQE/g, and the highest antioxidant activity was obtained by maceration extraction which produced an IC50 value of 5.20 µg/mL.